Perbandingan efek klonidin 2g/Kg intravena dan lidokain 2% 1.5 mg/Kg intravena untuk mencegah kenaikan tekanan intra okuler (TIO) selama tindakan intubasi endotrakheal - Muhammad Jalaluddin Assuyuthi Chalil; Nazaruddin Umar; Dadik Wahyu Wijaya; Aslim Sihotang (Fakultas Kedokteran USU, 2014)
Background: Endotracheal intubation is routinely performed during general anaesthesia in patients undergoing intraocular surgery. However, intubation is associated with an increase in intraocular pressure (IOP).Aim: To compare the effect of clonidine and lidocain to prevent the increase of IOP during endotracheal intubation. Method: Forty patients with no pre-existing eye diseaseundergoing elective non-ophthalmic surgeriesundergeneral anesthesiawererandomly allocated to two groups of 20 each.In Group A, patients received clonidine 2μg/kg/iv, and in group B lidocain2% 1.5mg/kg/iv for premedication.The hemodynamic profile (systolic and diastolic blood pressure, mean arterial pressure, heart rate) and IOP (using Schioetz tonometer) were measured before premedication (pre anesthesia), before intubation, immediately after intubation, and every 1 minute for 2 minutes.Result:There was a significant decrease in IOP and hemodynamic profile within both groups before and after endotracheal intubation compare to pre anesthesia periode (P <0.05). But the decreasewas not different between two groups (P >0.05). Conclusion: We conclude that both drugs have the same ability in blunting the hemodynamic response and attenuating the IOP, and preventing the increase in IOP caused by endotracheal intubation.Key word : clonidine, endotracheal intubation, intra-ocular pressure, lidocain